Non-Newtonian Endothelial Shear Stress Simulation: Does It Matter? - Thondapu, Vikas; Shishikura, Daisuke; Dijkstra, Jouke; Zhu, Shuang J.; Revalor, Eve; Serruys, Patrick W.; van Gaal, William J.; Poon, Eric K. W.; Ooi, Andrew; Barlis, Peter (Frontiers in Cardiovascular Medicine, 2022)
Patient-specific coronary endothelial shear stress (ESS) calculations using Newtonian and non-Newtonian rheological models were performed to assess whether the common assumption of Newtonian blood behaviour offers similar results to a more realistic but computationally expensive non-Newtonian model. 16 coronary arteries (from 16 patients) were reconstructed from optical coherence tomographic (OCT) imaging. Pulsatile CFD simulations using Newtonian and the Quemada non-Newtonian model were performed. Endothelial shear stress (ESS) and other indices were compared. Exploratory indices including local blood viscosity (LBV) were calculated from non-Newtonian simulation data. Compared to the Newtonian results, the non-Newtonian model estimates significantly higher time-averaged ESS (2.04±0.63Pa versus 1.59±0.54Pa, 95% CI 0.39-0.49, p<0.001) and ESS gradient (1.65±0.92Pa/mm versus 1.37±0.78Pa/mm, 95% CI 0.20-0.37.16, p<0.001) throughout the cardiac cycle, under-estimating the low ESS (<1Pa) area (37.20±13.57% versus 50.43±14.16%, 95% CI 11.28-15.18, p<0.001). Similar results were also found in the idealised artery simulations with non-Newtonian median ESS being higher than the Newtonian median ESS (healthy segments: 0.8238Pa versus 0.6618Pa, p<0.001 proximal; 0.8179Pa versus 0.6610Pa, p<0.001 distal; stenotic segments: 0.8196Pa versus 0.6611Pa, p<0.001 proximal; 0.2546Pa versus 0.2245Pa, p<0.001 distal) On average, the non-Newtonian model has a LBV of 1.45 times above the Newtonian model with an average peak LBV of 40-fold. Non-Newtonian blood model estimates higher quantitative ESS values than the Newtonian model. Incorporation of non-Newtonian blood behaviour may improve the accuracy of ESS measurements. The non-Newtonian model also allows calculation of exploratory viscosity-based hemodynamic indices, such as local blood viscosity, which may offer additional information to detect underlying atherosclerosis.